The impact of white collar crime in Malaysia / Adibah Shakinah Mohd Zakee - Mohd Zakee, Adibah Shakinah (2013)
In Malaysia, white-collar crime has been one of the serious cases occurred. White-collar crime can exist in many forms. In that case, Gottschalk (2010) admitted that, white-collar crime has been categorized into four main forms, which are corruption, fraud, theft, and manipulation. Besides that, Edelhertz (1970) also have given appropriate definition of whitecollar crime. In Edelhertz (1970, p.3) findings, crime is defined as an illegal act or series of illegal acts committed by non-physical means and by concealment or guile to obtain money or property, to avoid the payment or loss of money or property, or to obtain business or personal advantage. The United States is currently in the midst of a recession that some analysts believe will be the longest lasting economic downturn since the Great Depression. Various indicators of economic health such as the unemployment rate and foreclosures have reached their worst showings in decades over the past few months. The troubled state of the economy has received the long-standing debate concerning whether economic factors can be linked to increases in the nation’s crime rates